2020
DOI: 10.3390/ijms21082810
|View full text |Cite
|
Sign up to set email alerts
|

Acetylated Polysaccharides From Pleurotus geesteranus Alleviate Lung Injury Via Regulating NF-κB Signal Pathway

Abstract: The present work investigated the anti-inflammatory, antioxidant, and lung protection effects of acetylated Pleurotus geesteranus polysaccharides (AcPPS) on acute lung injury (ALI) mice. The acetylation of AcPPS was successfully shown by the peaks of 1737 cm−1 and 1249 cm−1 by FTIR. The animal experiments demonstrated that lung damage can be induced by zymosan. However, the supplementation of AcPPS had potential effects on reducing lung index, remitting inflammatory symptoms (TNF-α, IL-1β, and IL-6), inhibitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 48 publications
(100 reference statements)
0
4
0
Order By: Relevance
“…This suggests that inflammatory cell infiltration and fibrosis in the lung increase lung weight. In an animal model of acute lung injury, Song et al [ 36 ] reported an increase in lung weight and index. Cowley et al [ 37 ] stated that BLM-induced mice increased lung weight due to increased inflammation, fluid accumulation, and lung fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that inflammatory cell infiltration and fibrosis in the lung increase lung weight. In an animal model of acute lung injury, Song et al [ 36 ] reported an increase in lung weight and index. Cowley et al [ 37 ] stated that BLM-induced mice increased lung weight due to increased inflammation, fluid accumulation, and lung fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…MDA, as the final production of lipid peroxidation, is typically taken as an important indicator for oxidative stress ( Khaliq et al, 2018 ). And, the T-AOC capacity was considered as a measure of antioxidant defense system functions, which are recently used to monitor the development and extent of damage due to oxidative ( Song et al, 2020 ). Thus, the levels of the MDA and T-AOC and activates of these antioxidants were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Also Phosphorylated polysaccharides improved the physicochemical properties of native polysaccharides and enhanced their biological activity, or even imparting novel biological activity (Xia et al, 2021). Acetylated polysaccharides were suitable for natural food for prevention or remission in acute lung injury (Song et al, 2020).…”
Section: Discussionmentioning
confidence: 99%